The Impact of Counseling on Patient Compliance with Antihypertensive Medication: A Literature Review - Iskandar Jioe, Yulius; Patonah, Patonah; Mulyani, Yani (Jurnal Health Sains, 2024)
Hypertension is one of the main risk factors for heart problems. Apart from causing heart failure, hypertension can result in kidney failure and cerebrovascular disease. Patient behavior with high sodium and fat intake, unhealthy lifestyle and low compliance with taking antihypertensive medication can result in the failure to achieve therapeutic goals resulting in a decrease in the quality of life of hypertensive patients. Therefore, a method is needed to improve these things, one of which is the counseling method. The counseling method used is medication-taking counseling. The results of this research use the journal review method by analyzing 6 national journals and inter national journals. The results of the study explain that non-adherence to antihypertensive treatment not only has a major impact on blood pressure control, but also on cardiovascular morbidity and mortality. Therefore, clinical pharmacy services provided by pharmacists in pharmacies in the form of counseling are very important to achieve success. Various studies show that counseling provided by pharmacists and PILS (Patient Information Leaflets) has an influence on the level of compliance in taking anti-hypertension medication.